2019
DOI: 10.1002/adtp.201900012
|View full text |Cite
|
Sign up to set email alerts
|

A Tungsten Nitride‐Based O2 Self‐Sufficient Nanoplatform for Enhanced Photodynamic Therapy against Hypoxic Tumors

Abstract: The hypoxic microenvironment of tumors is a natural barrier to photodynamic therapy (PDT) and closely related to the tumor metastasis. Here, chlorine e6 (Ce6) decorated tungsten nitride nanoparticles (WN NPs) with a folic acid (FA) modification are fabricated to produce FA-WN-Ce6 (FWC) NPs for enhanced photodynamic therapy against hypoxic tumors. FWC NPs can efficiently accumulate in tumor sites via FA-mediated specific tumor targeting. With 630 nm laser irradiation, the WN in FWC can act as a photocatalyst fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In contrast, the cell viabilities for FWC NPs were less than 30% in both normoxia and hypoxia at the same Ce6 concentration (4 µg mL −1 ). To conclude, FWC NPs could have an excellent PDT effect in hypoxic tumor tissues (135).…”
Section: Tungstenmentioning
confidence: 98%
“…In contrast, the cell viabilities for FWC NPs were less than 30% in both normoxia and hypoxia at the same Ce6 concentration (4 µg mL −1 ). To conclude, FWC NPs could have an excellent PDT effect in hypoxic tumor tissues (135).…”
Section: Tungstenmentioning
confidence: 98%
“…C 5 N 2 nanoparticles [ 109 ], C 3 N 4 [ 110 , 111 ], tungsten nitride [ 112 ], carbon nanodot [ 113 ], graphdiyne oxide [ 114 ], iron disulfide (FeS 2 ) [ 115 ], cobalt phytate [ 116 ], etc., have been used in the water-splitting strategy. C 3 N 4 -related materials have been intensively studied for the enhancement of PDT via water splitting-mediated oxygen generation.…”
Section: Strategies For Modulating Tumor Hypoxia In Pdtmentioning
confidence: 99%
“…Zheng et al decorated a C 3 N 4 nanocomposite with carbon dots that enhanced red light absorption and showed that the decorated nanocomposite efficiently produced oxygen from water [ 56 ]. Wang et al also introduced the tungsten nitride (WN)-based nanomaterial that was originally designed for green energy application via water splitting to provide oxygen support to oxygen-enhanced PDT against hypoxic tumors [ 57 , 58 ]. Unlike semiconductor photocatalysts, WN with metallic properties could photocatalyze overall water splitting at longer wavelengths, up to 765 nm, which is suitable for in vivo oxygen production via water splitting due to the better light penetration.…”
Section: Oxygen Replenishing Strategiesmentioning
confidence: 99%